Two dimensional numerical and experimental models for the study of structure–soil–structure interaction involving three buildings. (1st April 2015) - Aldaikh, Hesham; Alexander, Nicholas A.; Ibraim, Erdin; Oddbjornsson, Olafur
Highlights: We model the dynamic interactions through ground of closely spaced buildings. We validate this model with experimental shake table tests. We explore the beneficial and adverse system geometries. Central buildings flanked by adjacent taller buildings are adversely effected. Abstract: This paper explores the adverse and beneficial effects of structure–soil–structure interaction (SSSI) under seismic excitation on a group of three buildings. A simple discrete formulation of the problem is employed that uses rotational interaction springs between buildings. A physical experimental shake-table test program is used to qualitatively validate the discrete theoretical model. Subsequently, a numerical study is performed which demonstrates that the central building in a three building case can act as a tuned mass damper for its adjacent buildings. Results indicated that this adverse effect can be more pronounced than the case where there are just two buildings interacting.